Forced vibration test of a building with semi-active damper system. - Kurata, Narito (Earthquake engineering & structural dynamics.)
The authors developed a semi active hydraulic damper (SHD) and installed it in an actual building in 1998. This was the first application of a semi-active structural control system that can control a building's response in a large earthquake by continuously changing the device's damping coefficient. A forced vibration test was carried out by an exciter with a maximum force of 100 kN to investigate the building's vibration characteristics and to determine the system's performance. As a result, the primary resonance frequency and the damping ratio of a building that the SHDs were not jointed to, decreased as the exciting force increased due to the influence of non-linear members such as PC curtain walls. The equivalent damping ratio was estimated by approximating the resonance curves using the steady state response of the SDOF bilinear hysteretic system. After the eight SHDs were jointed to the building, the system's performance was identified by a response control test for steady state vibration. The elements that composed the semi-active damper system demonstrated the specified performance and the whole system operated well.